PENGARUH 2,4-DICHLOROPHENOXYACETIC ACID (2,4-D) DAN BENZYL AMINO PURINE (BAP) TERHADAP INDUKSI TUNAS DARI EKSPLAN Folium DAN Petiolus communis TANAMAN DUKU (Lansium domesticum Corr.) - Siti Zulaikha; Jumiani Sarianti; Miftah Amaria Wulandari; Sherina Silva; Zaky Nuron Rizky; Amin Nurokhman; Arif Yachya (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2022)
Duku (Lansium domesticum Corr.) is an endemic plant of Indonesia that has a distinctive taste and is beneficial in the health sector. Besides that, the demand for duku seeds is increasing, so it is proven by the rapid propagation technique on a large scale. This can be achieved through tissue culture techniques. This study aimed to determine the effect of the growth regulators 2,4-D and BAP on Folium explants and Petiolus communis explants in inducing shoots. Leaf explants and leaf stalks were initiated using WPM (Woody Plant Medium) media with 4 different combinations of concentrations of growth regulators 2,4-D and BAP consisting of 0.0 ppm (2.4-D) + 0.0 ppm (BAP); 0.2 ppm (2.4-D) + 2.0 ppm (BAP); 0.2 ppm (2.4-D) + 2.5 ppm (BAP); 0.2 ppm (2.4-D) + 3.0 ppm (BAP) -D) + 2.0 ppm (BAP) on Petiolus communis explants is the most optimal combination of growth regulators, this is indicated by the growth response of the explants, namely the formation of brownish yellow callus on the explants.